Causes of Unwarranted Variation and Disparity in Breast Cancer Management in Regional and Rural Area - Kimberley J. Davis; Chantal Campbell; Rebekah Costelloe; Ting Song; Glaucia Fylyk; Ping Yu; Steven J. Craig (Hindawi-Wiley, 2024)
Introduction. Breast cancer management is complex, requiring personalised care from multidisciplinary teams. Research shows that there is unwarranted clinical variation in mastectomy rates between rural and metropolitan patients; that is, variation in treatment which cannot be explained by disease progression or medical necessity. This study aims to determine the clinical and nonclinical factors contributing to any unwarranted variation in breast cancer management in rural patients and to evaluate how these factors and variations relate to patient outcomes. Methods. Comprehensive data from patients who had primary breast cancer surgery from 2010 to 2014 in either a rural or metropolitan location in a single local health district was analysed (n = 686). Records were subset into two rurality groupings based on the postcode in which the patient resided, and the Modified Monash Model (MMM), an Australian system for classifying rurality. Statistical analysis was used to compare rural and metropolitan cohorts on treatments, patient characteristics, timeliness, and outcomes (recurrence and survival). Results. Rural patients had higher mastectomy rates than metropolitan patients (57% vs. 34%, p<0.001), despite a lack of difference in clinical or demographic factors accounting for such variation. The length of time between treatment pathway stages was consistently longer amongst rural patients (p<0.01). Rural women also had worse survival outcomes, especially amongst HER2-positive patients who had significantly lower survival (5-year 74% vs 82%; 10-year 49% vs 71%, p<0.05) than metropolitan HER2-positive patients. Conclusion. This study reveals clinical disparities among rural breast cancer patients, that cannot be explained by demographic and clinical factors alone. Rural patients face lower rates of breast-conserving surgery and treatment delays, attributable to systemic barriers such as limited access to specialist care, high travel costs, and suboptimal care coordination. These findings have important implications for improving equity and collaboration in delivering person-centred breast cancer care.